A method for preparing active regenerated micro-powder based on induced mineralization regulation and composite excitation

CN123003176APending Publication Date: 2026-10-30ANHUI TRANSPORTATION HLDG GRP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611497708.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

该方法只能提高再生微粉固碳性能,无法达到提高再生微粉活性的要求

Benefits of technology

1.本发明制得诱导矿化剂能够吸附在再生微粉表面,在二氧化碳环境中能够调控再生微粉进行碳化,促进再生微粉碳化过程中碳酸钙的生成。因甲基硅酸钠封端的诱导矿化剂在再生微粉的碳化过程中进行了调控,促进了后续与复合激发的协同作用,促进了钙矾石的延迟分解,提高了再生微粉的活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003176A_ABST
    Figure CN123003176A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of waste concrete, and provides a method for preparing active regenerated micro powder based on induced mineralization regulation and composite excitation, in which a prepolymer is obtained by polymerization reaction of polyhydric alcohol, diisocyanate and functional monomer as raw materials, then a capping agent is added to the prepolymer for capping, and finally an induced mineralization agent is obtained by neutralization and emulsification; the induced mineralization agent is mixed with the regenerated micro powder to obtain modified regenerated micro powder, the modified regenerated micro powder is placed in a closed space and continuously supplied with carbon dioxide-containing gas for carbonization to obtain carbonized regenerated micro powder, and the carbonized regenerated micro powder is mixed with polyaluminum sulfate and sulfate for activation to obtain active regenerated micro powder. The present application utilizes the induced mineralization agent to regulate the carbonization of the regenerated micro powder in the carbon dioxide environment, promotes the generation of high-crystallinity calcium carbonate in the carbonization process of the regenerated micro powder, and combines the polyaluminum sulfate and sulfate to synergistically excite the carbonized regenerated micro powder, thereby strengthening the delayed decomposition effect of ettringite and promoting the activation of the regenerated micro powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of waste concrete technology, specifically to a method for preparing active regenerated micro powder based on induced mineralization regulation and composite activation. Background Technology

[0002] The amount of waste concrete generated is increasing year by year, and its disposal methods are mainly stockpiling or landfilling, which occupies a large amount of land resources and damages the ecological environment. In the existing technology, recycled coarse aggregate and recycled fine aggregate, which are products of waste concrete recycling, have been applied in low-strength engineering, but the utilization efficiency of recycled micro powder is still relatively low.

[0003] In the activation treatment of recycled micro powder, existing technologies typically employ carbonation or composite activation methods. During carbonation, the recycled micro powder reacts with carbon dioxide to produce products such as calcium carbonate and silica gel; sulfate activation primarily enhances the strength of the system by promoting the formation of ettringite in cement-based materials. Existing literature discloses techniques that directly carbonize the recycled micro powder, followed by the addition of polyaluminum sulfate and sodium sulfate for composite activation. This can delay the decomposition of ettringite through the carbonation products, thereby increasing the system strength and activating the recycled micro powder. However, these methods all suffer from low carbonation efficiency and poor calcium carbonate crystal structure, affecting the synergistic effect of the carbonation products and composite activators, thus limiting the effectiveness of improving the activity of the recycled micro powder.

[0004] Chinese invention patent document CN115433337A discloses an inducing mineralizer and its application in promoting carbon fixation of regenerated micropowder. The method involves treating regenerated micropowder with this inducing mineralizer, utilizing its ability to induce the adsorption of calcium and carbonate ions on the surface of the micropowder to promote rapid mineralization and achieve efficient carbon dioxide absorption and fixation, thus realizing the resource utilization and carbon fixation of solid waste. However, this method only improves the carbon fixation performance of the regenerated micropowder and cannot meet the requirement of improving its activity. Summary of the Invention

[0005] The technical problem to be solved by this invention is how to improve the activity of regenerated micro powder.

[0006] The present invention solves the above-mentioned technical problems through the following technical means: This invention provides a method for preparing active regenerated micropowders based on induced mineralization regulation and composite activation, comprising the following steps: S1. A prepolymer is obtained by polymerization reaction using polyol, diisocyanate, and functional monomer as raw materials. An end-capping agent is then added to the prepolymer for end-capping, followed by neutralization and emulsification to obtain an inducing mineralizer. The polyol is one or more of polypropylene glycol, polyethylene glycol, and polytetrahydrofuran glycol. The end-capping agent is sodium methylsilicate. Sodium methylsilicate accounts for 50%–90% of the molar percentage of unreacted diisocyanate NCO groups. The mass ratio of polyol to diisocyanate is 1–3.5:1. The mass ratio of functional monomer to diisocyanate is 0.05–0.5:1. The functional monomer is one or more of N,N'-dimethylethylenediamine, 1,2-diaminoethylguanidine, and amidoethylenediamine. S2. The inducing mineralizer is mixed with the regenerated micro powder to obtain modified regenerated micro powder. The modified regenerated micro powder is placed in a closed space and continuously purged with a gas containing carbon dioxide to obtain carbonized regenerated micro powder. The carbonized regenerated micro powder is mixed with polyaluminum sulfate and sulfate to activate it to obtain activated regenerated micro powder. The mass ratio of the inducing mineralizer to the regenerated micro powder is 0.005~0.03:1; the mass ratio of carbonized regenerated micro powder, polyaluminum sulfate and sulfate is 1:0.01~0.06:0.01~0.08.

[0007] Preferably, the molecular weight of the polyol is 500 to 2000.

[0008] Preferably, the diisocyanate is one or more of isophorone diisocyanate, hexamethylene diisocyanate, and dicyclohexylmethane diisocyanate.

[0009] Preferably, the recycled micro powder is particles with a particle size of less than 150 micrometers produced during the crushing of waste concrete.

[0010] Preferably, the mixing time is 0.1 to 1.5 hours.

[0011] Preferably, the temperature in the enclosed space is 15~50℃ and the humidity in the enclosed space is 20~90%.

[0012] Preferably, the volume fraction of carbon dioxide in the enclosed space is 10-60%.

[0013] Preferably, the carbonization time is 0.3~10h.

[0014] Preferably, the sulfate is one or more of calcium sulfate, sodium sulfate, and potassium sulfate.

[0015] Preferably, the activation time is 0.1~1.5h.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The mineralizing agent prepared by this invention can be adsorbed on the surface of regenerated micro powder. In a carbon dioxide environment, it can regulate the carbonization of the regenerated micro powder and promote the formation of calcium carbonate during the carbonization process. Because the sodium methylsilicate-terminated mineralizing agent regulates the carbonization process of the regenerated micro powder, it promotes the synergistic effect of subsequent composite activation, promotes the delayed decomposition of ettringite, and improves the activity of the regenerated micro powder.

[0017] 2. This invention adsorbs an inducing mineralizer onto the surface of regenerated micropowder. The inducing mineralizer, in a carbon dioxide environment, regulates the carbonization of the regenerated micropowder, promoting the formation of highly crystalline calcium carbonate during the carbonization process. Furthermore, polyaluminum sulfate and sulfates are combined to synergistically activate the carbonization of the regenerated micropowder, enhancing the delayed decomposition effect of ettringite and promoting the activation of the regenerated micropowder, resulting in active regenerated micropowder. Simultaneously, the active regenerated micropowder prepared by this invention promotes the fixation of carbon dioxide by the regenerated micropowder.

[0018] 3. This invention, by inducing mineralization to regulate the carbonization of regenerated micro powder, can significantly optimize the carbonization reaction process of regenerated micro powder. Compared with existing carbonization methods for regenerated micro powder, this invention can significantly improve the crystal structure and yield of calcium carbonate in the carbonization product. Moreover, the process steps are simple, low-carbon and environmentally friendly, and can greatly increase the amount of carbon dioxide fixed by regenerated micro powder, thus having broad prospects for industrial application.

[0019] 4. This invention can significantly improve the activity of recycled micro powder. By combining the activation of recycled micro powder with the synergistic activation of polyaluminum sulfate and sulfate, this invention can enhance the delayed decomposition effect of ettringite in recycled micro powder, give full play to its reinforcing role, and thus improve the mechanical strength of composite cement. Compared with the existing recycled micro powder activation technology, this invention has better activation efficiency and helps to solve the problems of high difficulty and low utilization rate of recycled micro powder resources at present. Attached Figure Description

[0020] Figure 1 Thermogravimetric analysis diagrams of the carbonized regenerated micro powders in Example 1 and Comparative Example 1 of this invention; Figure 2 Thermogravimetric analysis (TGA) diagrams of the carbonized regenerated micropowders in Example 2 and Comparative Example 5 of this invention; Figure 3 The images show the XRD patterns of the powders prepared in Examples 1, 3, 2 and 6 of this invention. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] Unless otherwise specified, all test materials and reagents used in the following examples are commercially available.

[0023] Unless otherwise specified in the embodiments, the techniques or conditions described in the literature in this field or in accordance with the product manual may be followed.

[0024] The recycled micropowder used in this embodiment and comparative example consists of particles with a diameter of less than 150 micrometers generated during the crushing of waste concrete.

[0025] Example 1 This embodiment provides a method for preparing active regenerated micro powder based on induced mineralization regulation and composite activation, specifically including the following steps: S1. Preparation of mineralizing agent At 80°C, 10 parts by mass of propylene glycol with a molecular weight of 500, 5.5 parts by mass of isophorone diisocyanate, and 0.825 parts by mass of N,N'-dimethylethylenediamine were subjected to a prepolymerization reaction in a stirred reactor for 4 hours to obtain a prepolymer. The molar number of unreacted diisocyanate NCO groups during the prepolymerization reaction was confirmed by titration. Subsequently, the prepolymer was end-capped with sodium methylsilicate, which accounted for 50% of the molar percentage of unreacted diisocyanate NCO groups. The end-capped prepolymer was cooled to room temperature, and a saturated aqueous solution of CO2 was added to it. The mixture was mechanically stirred at 1500 rpm for 30 min to obtain an inducing mineralizer.

[0026] S2, Preparation of active regenerated micro powder The inducing mineralizer and the regenerated micro powder were mixed at a mass ratio of 0.007:1 for 0.2 h to obtain modified regenerated micro powder. The modified regenerated micro powder was placed in a sealed space at 20°C for 8 h for carbonization. During the carbonization process, carbon dioxide gas with a volume fraction of 10% was continuously introduced, and the humidity in the sealed space was 30% to obtain carbonized regenerated micro powder. The carbonized regenerated micro powder was mixed with polyaluminum sulfate and calcium sulfate at a mass ratio of 1:0.04:0.02 for 0.5 h to obtain active regenerated micro powder.

[0027] Example 2 This embodiment provides a method for preparing active regenerated micro powder based on induced mineralization regulation and composite activation, specifically including the following steps: S1. Preparation of mineralizing agent At 80°C, 9 parts by mass of polytetrahydrofuran glycol with a molecular weight of 500, 4.5 parts by mass of hexamethylene diisocyanate, and 2 parts by mass of 1,2-diaminoethyl guanidine were subjected to a prepolymerization reaction in a stirred reactor for 4 hours to obtain a prepolymer. The molar number of NCO groups in the diisocyanate during the prepolymerization reaction was confirmed by titration. Subsequently, the prepolymer was end-capped with sodium methylsilicate, which accounted for 50% of the molar percentage of unreacted NCO groups in the diisocyanate. The end-capped prepolymer was cooled to room temperature, and a saturated aqueous solution of CO2 was added to it. The mixture was mechanically stirred at 1500 rpm for 30 minutes to obtain an inducing mineralizer.

[0028] S2, Preparation of active regenerated micro powder The inducing mineralizer and regenerated micro powder were mixed at a mass ratio of 0.025:1 for 1.0 h to obtain modified regenerated micro powder. The modified regenerated micro powder was placed in a sealed space at 40°C for 5 h for carbonization. During the carbonization process, carbon dioxide gas with a volume fraction of 50% was continuously introduced, and the humidity in the sealed space was 70% to obtain carbonized regenerated micro powder. The carbonized regenerated micro powder was mixed with polyaluminum sulfate and sodium sulfate at a mass ratio of 1:0.04:0.02 for 1.5 h to obtain active regenerated micro powder.

[0029] Example 3 This embodiment provides a method for preparing active regenerated micro powder based on induced mineralization regulation and composite activation, specifically including the following steps: S1. Preparation of mineralizing agent At 80°C, 9 parts by mass of polytetrahydrofuran glycol with a molecular weight of 500, 4.5 parts by mass of dicyclohexylmethane diisocyanate, and 2 parts by mass of amidine ethylenediamine were subjected to a prepolymerization reaction in a stirred reactor for 4 hours to obtain a prepolymer. The molar number of unreacted diisocyanate NCO groups during the prepolymerization reaction was confirmed by titration. Subsequently, the prepolymer was end-capped with sodium methylsilicate, wherein the sodium methylsilicate accounted for 90% of the molar percentage of unreacted diisocyanate NCO groups. The end-capped prepolymer was cooled to room temperature, and a saturated aqueous solution of CO2 was added to it. The mixture was mechanically stirred at 1500 rpm for 30 min to obtain an inducing mineralizer.

[0030] S2, Preparation of active regenerated micro powder The inducing mineralizer and regenerated micro powder were mixed at a mass ratio of 0.01:1 for 1.5 hours to obtain modified regenerated micro powder. The modified regenerated micro powder was placed in a sealed space at 15°C for 1 hour for carbonization. During the carbonization process, carbon dioxide gas with a volume fraction of 60% was continuously introduced, and the humidity in the sealed space was 50% to obtain carbonized regenerated micro powder. The carbonized regenerated micro powder was mixed with polyaluminum sulfate and potassium sulfate at a mass ratio of 1:0.02:0.06 for 0.5 hours to obtain active regenerated micro powder.

[0031] Comparative Example 1 This comparative example provides a method for preparing active regenerated micro powder based on induced mineralization regulation and composite activation. The difference between this comparative example and Example 1 is that sodium methylsilicate is replaced with ethanol in S1 to obtain induced mineralizer and active regenerated micro powder.

[0032] Comparative Example 2 This comparative example provides a method for preparing active regenerated micro powder based on induced mineralization regulation and composite activation. The difference between this comparative example and Example 1 is that sodium methylsilicate is replaced with propanol in S1 to obtain induced mineralizer and active regenerated micro powder.

[0033] Comparative Example 3 This comparative example provides a method for preparing activated and regenerated micro powder, the specific steps of which are as follows: The regenerated micro powder was placed in a sealed space at 20°C for 8 hours for carbonization. During the carbonization process, carbon dioxide gas with a volume fraction of 10% was continuously introduced, and the humidity in the sealed space was 30%. Carbonized regenerated micro powder was obtained. The carbonized regenerated micro powder was mixed with polyaluminum sulfate and calcium sulfate at a mass ratio of 1:0.04:0.02 for 0.5 hours to obtain active regenerated micro powder.

[0034] Comparative Example 4 This comparative example provides a method for preparing activated and regenerated micro powder, the specific steps of which are as follows: The regenerated micro powder was mixed with polyaluminum sulfate and calcium sulfate at a mass ratio of 1:0.04:0.02 for 0.5 h to obtain active regenerated micro powder.

[0035] Comparative Example 5 This comparative example provides a method for preparing active regenerated micro powder based on induced mineralization regulation and composite activation. The difference between this comparative example and Example 2 is that sodium methylsilicate is replaced with propanol in S1 to obtain induced mineralizer and active regenerated micro powder.

[0036] Comparative Example 6 This comparative example provides a method for preparing activated and regenerated micro powder, the specific steps of which are as follows: The regenerated micro powder was placed in a sealed space at 40°C for 5 hours for carbonization. During the carbonization process, carbon dioxide gas with a volume fraction of 50% was continuously introduced, and the humidity in the sealed space was 70%. Carbonized regenerated micro powder was obtained. The carbonized regenerated micro powder was mixed with polyaluminum sulfate and sodium sulfate at a mass ratio of 1:0.04:0.02 for 1.5 hours to obtain active regenerated micro powder.

[0037] Comparative Example 7 This comparative example provides a method for preparing activated and regenerated micro powder, the specific steps of which are as follows: The regenerated micro powder was mixed with polyaluminum sulfate and sodium sulfate at a mass ratio of 1:0.04:0.02 for 1.5 h to obtain active regenerated micro powder.

[0038] Comparative Example 8 This comparative example provides a method for preparing active regenerated micropowder based on induced mineralization regulation and composite activation. The difference between this comparative example and Example 3 is that the method for preparing the induced mineralizer in S1 is different, as detailed below: At 80°C, 15.5 parts by weight of polypropylene glycol with a molecular weight of 1000, 5.5 parts by weight of hexamethylene diisocyanate, and 0.825 parts by weight of N,N dimethyl N',N' 2(2) Hydroxypropyl) 1,3 Propylene diamine was prepolymerized in a stirred reactor for 4 hours, followed by the addition of 0.55 parts by weight of 1,4-diamine. Butylene glycol was chain-extended for 2 hours to obtain a polyurethane prepolymer, which was then cooled to room temperature and subjected to 2,2 Dimethylolbutyric acid (DMPO) was reacted with polyurethane prepolymer as a salt-forming agent for 30 min, followed by emulsification with deionized water for 30 min to obtain an aqueous polyurethane emulsion, which served as an inducing mineralization agent. Finally, activated and regenerated micropowder was obtained.

[0039] Comparative Example 9 This comparative example provides a method for preparing activated and regenerated micro powder, the specific steps of which are as follows: The regenerated micro powder was placed in a sealed space at 15°C for 1 hour for carbonization. During the carbonization process, carbon dioxide gas with a volume fraction of 60% was continuously introduced, and the humidity in the sealed space was 50%. Carbonized regenerated micro powder was obtained. The carbonized regenerated micro powder was mixed with polyaluminum sulfate and potassium sulfate at a mass ratio of 1:0.02:0.06 for 0.5 hours to obtain active regenerated micro powder.

[0040] Comparative Example 10 This comparative example provides a method for preparing activated and regenerated micro powder, the specific steps of which are as follows: The regenerated micro powder was mixed with polyaluminum sulfate and potassium sulfate at a mass ratio of 1:0.02:0.06 for 0.5 h to obtain active regenerated micro powder.

[0041] Experimental Example 1. Thermogravimetric analysis was performed on the carbonized regenerated micropowders prepared in Example 1, Comparative Example 1, Example 2, and Comparative Example 5. The results are as follows: Figure 1 and Figure 2 As shown.

[0042] Calcium carbonate decomposes below 720℃ with lower crystallinity, while calcium carbonate decomposes between 720 and 950℃ with higher crystallinity. The calcium carbonate content is calculated by dividing the mass loss in the 600–720℃ and 720–950℃ temperature ranges by the decomposition coefficient 0.4396 (which represents the theoretical CO2 mass fraction in calcium carbonate). Figure 1 It can be seen that the content of highly crystalline calcium carbonate in Example 1 (23.2%) is significantly higher than that in Comparative Example 1 (16.9%). According to... Figure 2 It can be seen that the content of highly crystalline calcium carbonate in Example 2 (13.5%) is significantly higher than that in Comparative Example 5 (6.3%). At the same time, the total amount of calcium carbonate generated in Examples 1 and 2 is also higher than that in Comparative Example 1 and Comparative Example 5, respectively. This indicates that after the regenerated micro powder is carbonized by the inducing mineralizer of the present invention, the proportion of highly crystalline calcium carbonate and the content of calcium carbonate in the carbonization product of the regenerated micro powder are significantly increased.

[0043] 2. The active recycled micro-powder obtained from Examples 1, 3, 2, and 6, water, and ordinary silicate cement were mixed and stirred evenly at a mass ratio of 1:1:1.5 to obtain a composite cement paste. The composite cement paste was then ground into powder. XRD analysis of the powder was performed, and the results are as follows: Figure 3 As shown.

[0044] according to Figure 3 It can be seen that the peak value of 9.1° represents ettringite. The ettringite diffraction peak intensity of Examples 1 and 2 is significantly higher than that of Comparative Examples 3 and 6. This indicates that using the inducing mineralizer of the present invention in the recycled micro powder enhances the delayed decomposition effect of ettringite, further improves the strength of the composite cement, and thus improves the activity of the recycled micro powder.

[0045] 3. The activity index of the activated and regenerated micro powders prepared in Examples 1-3 and Comparative Examples 1-10 was determined. The specific method is as follows: The activated and regenerated micro powders, water and ordinary silicate cement were mixed and stirred evenly in a mass ratio of 1:1:1.5 to prepare a composite cement slurry. The composite cement slurry was poured into a 4mm×4mm×4mm mold and placed under standard curing conditions until the specified age to obtain composite cement. The composite cement was crushed and ground into powder, passed through a 0.075mm sieve and then subjected to XRD testing. The results are shown in Table 1.

[0046] Table 1 Activity Index of Active Regenerated Micropowder

[0047] As shown in Table 1, compared with existing methods using monohydroxy compound (ethanol or propanol) encapsulated mineralizing agents, direct carbonization, or no carbonization to obtain activated regenerated micropowder, the activity of the regenerated micropowder is significantly improved after carbonization with a sodium methylsilicate-terminated mineralizing agent, followed by combined activation with polyaluminum sulfate and sulfates. This indicates that the sodium methylsilicate-terminated mineralizing agent and the combined activation method proposed in this invention have high activation efficiency. This is because the sodium methylsilicate-terminated mineralizing agent is regulated during the carbonization process of the regenerated micropowder, thereby promoting the synergistic effect with subsequent combined activation, delaying the decomposition of ettringite, and thus improving the compressive strength of the composite cement.

[0048] 4. The activated and regenerated micropowders prepared in Examples 1-3 and Comparative Examples 1-10 were used to determine the amount of carbon dioxide remaining. The specific method is as follows: 2.00 g of activated and regenerated micropowder was weighed and heated at 500 °C for 1 h. The mass of the residue was measured as m1. The powder was then heated again at 900 °C for 1 h, and the mass of the residue was measured as m2. The mass loss between 500 and 900 °C was the amount of carbon dioxide remaining, calculated as (m1-m2) / m1×100%. The results are shown in Table 2.

[0049] Table 2 Carbon dioxide sequestration content of activated and regenerated micro powder

[0050] As shown in Table 2, the active regenerated micro powder of the present invention significantly increases the amount of carbon dioxide absorbed and fixed by the regenerated micro powder, indicating that the method of the present invention has a better effect on carbon fixation of regenerated micro powder than the existing carbonization method of regenerated micro powder induced by mineralizing agent encapsulated with monohydroxy compound.

[0051] To illustrate the activity-enhancing effect of the regenerated micropowder prepared by the present invention, the active regenerated micropowder prepared in the examples and comparative examples was used as an auxiliary cementitious material to determine its activity index. Specifically, comparing Example 1 with Comparative Examples 1, 2, and 5 demonstrates the difference in the effect of the inducing mineralizer capped with sodium methylsilicate in the present invention on the crystal form of the carbonized product of the regenerated micropowder compared to the inducing mineralizer encapsulated with a monohydroxy compound (ethanol or propanol).

[0052] The comparison between Example 1 and Comparative Example 3, and between Example 2 and Comparative Example 6, demonstrates that the mineralizing agent prepared by the present invention, when used in recycled micro powder, can induce mineralization of the recycled micro powder, enhance the delayed decomposition effect of ettringite, further improve the strength of composite cement, and thus improve the activity of recycled micro powder.

[0053] The comparison between Example 1 and Comparative Examples 3-4, Example 2 and Comparative Examples 6-7, and Example 3 and Comparative Examples 9-10 demonstrates that the active regenerated micro powder prepared by the present invention through controlled carbonization and composite activation can enhance the delayed decomposition effect of ettringite and the activation effect on the regenerated micro powder.

[0054] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing active regenerated micropowders based on induced mineralization regulation and composite activation, characterized in that, Includes the following steps: S1. A prepolymer is obtained by polymerization reaction using polyol, diisocyanate, and functional monomer as raw materials. An end-capping agent is then added to the prepolymer for end-capping, followed by neutralization and emulsification to obtain an inducing mineralizer. The polyol is one or more of polypropylene glycol, polyethylene glycol, and polytetrahydrofuran glycol. The end-capping agent is sodium methylsilicate. Sodium methylsilicate accounts for 50%–90% of the molar percentage of unreacted diisocyanate NCO groups. The mass ratio of polyol to diisocyanate is 1–3.5:

1. The mass ratio of functional monomer to diisocyanate is 0.05–0.5:

1. The functional monomer is one or more of N,N'-dimethylethylenediamine, 1,2-diaminoethylguanidine, and amidoethylenediamine. S2. The inducing mineralizer is mixed with the regenerated micro powder to obtain modified regenerated micro powder. The modified regenerated micro powder is placed in a closed space and continuously purged with a gas containing carbon dioxide to obtain carbonized regenerated micro powder. The carbonized regenerated micro powder is mixed with polyaluminum sulfate and sulfate to activate it to obtain activated regenerated micro powder. The mass ratio of the inducing mineralizer to the regenerated micro powder is 0.005~0.03:1; the mass ratio of carbonized regenerated micro powder, polyaluminum sulfate and sulfate is 1:0.01~0.06:0.01~0.

08.

2. The method for preparing active regenerated micropowder based on induced mineralization regulation and composite activation according to claim 1, characterized in that, The molecular weight of polyols ranges from 500 to 2000.

3. The method for preparing active regenerated micropowder based on induced mineralization regulation and composite activation according to claim 1, characterized in that, The diisocyanate is one or more of isophorone diisocyanate, hexamethylene diisocyanate, and dicyclohexylmethane diisocyanate.

4. The method for preparing active regenerated micropowder based on induced mineralization regulation and composite activation according to claim 1, characterized in that, The temperature in the enclosed space is 15~50℃, and the humidity is 20~90%.

5. The method for preparing active regenerated micropowder based on induced mineralization regulation and composite activation according to claim 1, characterized in that, The volume fraction of carbon dioxide in a confined space is 10-60%.

6. The method for preparing active regenerated micropowder based on induced mineralization regulation and composite activation according to claim 1, characterized in that, The mixing time is 0.1~1.5h.

7. The method for preparing active regenerated micropowder based on induced mineralization regulation and composite activation according to claim 1, characterized in that, The carbonization time is 0.3~10h.

8. The method for preparing active regenerated micropowder based on induced mineralization regulation and composite activation according to claim 1, characterized in that, The activation time is 0.1~1.5h.

9. The method for preparing active regenerated micropowder based on induced mineralization regulation and composite activation according to claim 1, characterized in that, Sulfates are one or more of calcium sulfate, sodium sulfate, and potassium sulfate.

10. The method for preparing active regenerated micropowder based on induced mineralization regulation and composite activation according to claim 1, characterized in that, Recycled micro powder is particles with a diameter of less than 150 micrometers produced during the crushing of waste concrete.

Citation Information

Patent Citations

  • Inducing mineralizer and application thereof in inducing mineralization to promote regenerated micro powder carbon sequestration

    CN115433337A